Efficacy of a Community‐ Versus Primary Care–Centered Program for Childhood Obesity: TX CORD RCT. Issue 9 (13th July 2017) - Butte, Nancy F.; Hoelscher, Deanna M.; Barlow, Sarah E.; Pont, Stephen; Durand, Casey; Vandewater, Elizabeth A.; Liu, Yan; Adolph, Anne L.; Pérez, Adriana; Wilson, Theresa A.; Gonzalez, Alejandra; Puyau, Maurice R.; et al.
Abstract : Objective: This randomized controlled trial was conducted to determine comparative efficacy of a 12‐month community‐centered weight management program (MEND2‐5 for ages 2‐5 or MEND/CATCH6‐12 for ages 6‐12) against a primary care‐centered program (Next Steps) in low‐income children. Methods: Five hundred forty‐nine Hispanic and black children (BMI ≥ 85th percentile), stratified by age groups (2‐5, 6‐8, and 9‐12 years), were randomly assigned to MEND2‐5 (27 contact hours)/MEND/CATCH6‐12 (121.5 contact hours) or Next Steps (8 contact hours). Primary (BMI value at the 95th percentile [%BMIp95 ]) and secondary outcomes were measured at baseline, 3 months (Intensive Phase), and 12 months (Transition Phase). Results: For age group 6‐8, MEND/CATCH6‐12 resulted in greater improvement in %BMIp95 than Next Steps during the Intensive Phase. Effect size (95% CI) was −1.94 (−3.88, −0.01) percentage points ( P  = 0.05). For age group 9‐12, effect size was −1.38 (−2.87, 0.16) percentage points for %BMIp95 ( P  = 0.07). MEND2‐5 did not differentially affect %BMIp95 . Attendance averaged 52% and 22% during the Intensive and Transition Phases. Intervention compliance was inversely correlated to change in %BMIp95 during the Intensive Phase ( P  < 0.05). In the Transition Phase, %BMIp95 was maintained or rebounded in both programs ( P  < 0.05). Conclusions: MEND/CATCH6‐12 was more efficacious for BMI reduction at 3 months but not 12 months compared to Next Steps in underserved children. Intervention compliance influenced outcomes, emphasizing the need for research in sustaining family engagement in low‐income populations.